Source rock characterization and oil grouping in the NW Java, Central Java and NE Java Basins, Indonesia - Ragil Pratiwi (Ikatan Ahli Geologi Indonesia, 2021)
This study reveals the detailed organic geochemistry from crude oils (acquired from wells and seepages) and rock extracts from NW Java and NE Java Basin that have been gathered and compiled from previous publications. The interpretation was conducted from geochemical data value and plot, GC-MS fingerprints, and agglomerative-hierarchical cluster analysis using the Euclidean algorithm. Various source rocks from those basins were deposited under fluvio-lacustrine to the marine environment. Six groups of crude oils are also distinguished. Groups 1, 2, and 6 are oils from deltaic source rocks, Groups 3 and 4 are oils from marine source rocks, and Group 5 is from lacustrine and/or fluvio-lacustrine source rocks. Groups 1, 2, and 6 could be distinguished from the pristane/phytane (Pr/Ph) ratio and C29 sterane composition, while Groups 3 and 4 differ from the distribution of C27 sterane. The schematic depositional environment of source rocks is also generated from this study and suggests that Group 5 is deposited during early syn-rift non-marine settings, while the remaining groups are deposited in the deltaic (Group 1,2 and 6) and marine settings (Groups 3 and 4). The main differences between those groups are including the distributions of C27-C28-C29 steranes.